Application of the continuous green-t (CGT) intersection concept at signalized intersection to support sustainable mobility in peatland area - Rizqy Ridho Prakasa; Dika Meilisan; Edi Yusuf Adiman; Niskan Walid Masruri; Novreta Ersyi Darfia; Randhi Saily; Intan Monica MG; Vinka Lyona; Benny Hamdi Rhoma Putra; Safridatul Audah; Soewignjo Agus Nugroho (Journal of Infrastructure Planning and Engineering, 2026)
The signalized intersection of Jl. HR. Soebrantas – Jl. SM. Amin is one of the congestion-prone intersections in Pekanbaru City, particularly due to its location in a peatland area. Peatland conditions, which are characterized by low bearing capacity and high compressibility, limit extensive physical expansion of road infrastructure. At the same time, this intersection serves as a key connector between major activity centers, including educational institutions, offices, commercial areas, and residential zones, resulting in significant traffic congestion and long queues, especially during peak hours. To address these challenges, this study proposes the implementation of a Continuous Green-T (CGT) intersection design as an operational and geometric solution that minimizes the need for large-scale infrastructure modification. The objective of this study is to evaluate the performance of the intersection after the implementation of the CGT design using microscopic traffic simulation with VISSIM. The analysis results indicate that the existing condition has an average delay of 62.5 seconds (Level of Service/LOS F), while the implementation of CGT reduces the average delay to 19.3 seconds (LOS C). This demonstrates that the CGT design is effective in reducing intersection delay by 43.2 seconds and improving the Level of Service from F to C, making it a suitable approach for traffic management in physically constrained environments such as peatland areas.